PEMANFAATAN HIDROLISIS ASAM DALAM MODIFIKASI PATI GARUT (Marantha Arundinacea) UNTUK PROSES MIKROENKAPSULASI ASAP CAIR - , IMAM SYAHFPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Arrowroot (Marantha arundinacea), is one of the root crops of the state of Indonesia. Generally used as traditional public consumption because of the sweetness or processed into flour or starch. However, these bulbs are less maintained its availability due to high market demand is not match by availability of raw material (arrowroot tubers), but the methos is fairy easy cultivation and adaptive nature of the plan led to the idea to try other alternatives in the arrowroot plan utilization as coating agent in the microencapsulation process. This study aims to find the best concentration of HCl to hydrolyze arrowroot starch, so it can be used as coating agent in microencapsulation process. In hydrolyze, arrowroot starch dissolved in HCl solvent by 30 : 100 ratio and variation HCl solvent in level of 0.3%